(untitled) (Bangladesh Journal of Infectious Diseases, 2020)
Background: Post-operative infection can occur after bone grafting among patietns with jaw cyst. Objective: The purpose of the present study was to compare the rate of infection as postoperative outcomes after hydroxyapatite and allogenic bone graft among jaw cyst patients. Methodology: This randomized clinical trial was conducted in the Department of Oral and Maxillofacial Surgery at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from July 2006 to June 2008. Patients presented with radicular and dentigerous cyst and relatively non infected cystic lesion were selected as study population. The study population were divided into two groups designed as Group A treated with with allogenic-bone graft and Group B treated with hydroxyapatite alloplastic material after enucleation of the cystic lesion. The rate of infection was recorded after surgery in both group A and B. Result: A total number of 28 patients were recruited for this study of which 14 patients were treated with hydroxyapatite crystals bone graft in group A and 14 patients were treated with allogenic bone graft in group B. Post-operative infection was not found in group A and 5(35.7%) in group B (p<0.05). Infection occurred in 1(20.0%) case in one side intact and 4(80.0%) in both side lost. Infection was found in 1(20.0%) case and 4(80.0%) cases in average and poor oral hygiene status respectively. Conclusion: In conclusion more infection occurs in allogenic bone graft group than the group treated with hydroxyapatite alloplastic material Bangladesh Journal of Infectious Diseases 2019;6(2):29-33